Economic Development Prospective Dairy Industry in Nepal: A Review - Laila, Nisful; Singh, Sanju Kumar; Das, Pankaj Kumar (International Journal of Psychosocial Rehabilitation, 2020)
This paper is review of Dairy related income in Nepal throughout several research paper that had published in some national and international articles, Nepal is one of Agriculture based country and still least developing country. It has huge potential to grow in various way one of the sector is Dairy Industry. Huge demand of dairy product like Milk, yoghurt, cheese. Dairy Industry of Nepal is lack of good quality and not modernized and its cause huge loss in economy of Nation. After reviewing the article, it is suggested that Nepal has wide range of economic potential in Dairy Industry. However, due to lack of traditional farming, lack of milk product commercialization and poor planning execution makes left behind the development of Diary sector development in Nepal.